Mining text on Coronavirus (2020)
This document describes the behavior of the production of academic papers and high circulation newspapers, published under the terms “Coronavirus, Covid-19 or SARS-CoV-2”. The purpose of this paper is to employ text mining techniques and qualitative data analysis for pattern identification (Dobrzyński, Dziekoński, Krzysztof, & Jurczuk, 2013; Westergaard, Staerfeldt, Tønsberg, Jensen, & Brunak, 2018). The interest of this study arises from the importance of this topic today and its relationship with the economy, business and society. As a result, the production of scientific papers has been led by the United States, China and Russia. In Latin America, Brazil is the country with the highest scientific output on this subject. The analysis of newspaper articles focusing on economic and business issues showed the work between large companies, the government and the community, as well as companies with businesses and the need to adapt to constant change in the face of the crisis of labor and production.